The Importance of the Montessori Method in Early Childhood Education in Ethnic Minority Regions: A Case Study of the Z Development Zone, Western China - Zhu, Jing Jing (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2024)
This study examines the significance of the Montessori method in early childhood education within ethnic minority regions, focusing on a case study in the Z Development Zone in Western China. Through qualitative research methods, including interviews with 19 kindergarten teachers, the study assesses the current state of the teaching workforce and the potential for the Montessori method to enhance education in these regions. The findings reveal that Montessori practices are not currently used in the studied kindergartens due to challenges such as an imbalanced teaching staff, low professional standards, and inadequate training opportunities. Supported by Social Representation (SR) theory, the analysis highlights the Montessori method’s focus on child autonomy and individual development, which aligns with the educational needs of ethnic minority areas. The research suggests that introducing Montessori principles could significantly improve the quality of education. To address existing issues, the study recommends strategies such as targeted teacher training, improving training quality, and raising the social status of kindergarten teachers. These measures aim to strengthen the educational infrastructure in ethnic minority regions and promote sustainable development in early childhood education.